Technical efficiency of Slovak general hospitals - Richard Kališ (University of Economics in Bratislava, Department of Economic Policy, 2018)
In this study, technical efficiency of Slovak general hospitals was investigated. The well-known non-parametric Data Envelopment Analysis was used to compare performance of Slovak health care providers. Results are based on four slightly differentiated models. Both CRS and VRS variation with different input approaches were used. Our results suggest low average efficiency in Slovak hospitals in the range 0.45 to 0.62 with great variations in efficiency score between individual Decision Making Units (DMUs). These results are relative without appropriate cross-country comparisons. Furthermore, in type of hospital entity there is no significant difference in efficiency score. However there is not a single efficient DMU in a group of municipality hospitals. Although, these results must be taken with caution due to questionable quality of data, this paper provides some valuable overview on technical efficiency of health care providers
Keywords: P41; G34; C44; 330; data envelopment analysis; hospitals; efficiency